Ultrafast coupling between light, coherent lattice vibrations, and the magnetic structure of semicovalent LaMnO(3). - Wall, S; Prabhakaran, D; Boothroyd, A; Cavalleri, A (2009)
Coherent lattice vibrations are excited and probed with pulses of 10 fs duration in LaMnO(3). The measured frequencies correspond to those of Jahn-Teller stretching and of out-of phase rotations of the oxygen octahedra. Surprisingly, the amplitude and damping rate of both modes exhibit a sharp discontinuity at the Néel temperature, highlighting nontrivial coupling between light, lattice, and magnetic structure. We explain this effect by applying the Goodenough-Kanamori rules to the excited state of LaMnO(3), and note that charge transfer can invert the sign of the semicovalent exchange interaction, which in turn perturbs the equilibrium bond lengths.